Green construction of attapulgite / sodium alginate porous cross-linked membrane and uranium separation / enrichment method of attapulgite / sodium alginate porous cross-linked membrane

By constructing a porous crosslinked membrane of concave rock stone/sodium alginate, the coordinated stability of nanoconcave rock stone and plant active ingredients is used to solve the problems of low uranium separation/enrichment efficiency and complex material preparation in water bodies, achieving high efficiency and environmental protection uranium separation effect and reduces the risk of environmental pollution.

CN119236908APending Publication Date: 2025-01-03LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734384.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art has problems such as low efficiency, high cost, and environmental pollution in the efficient separation/enrichment of uranium in water bodies. The preparation process of sodium alginate-based materials is complex and the cross-linking is uneven, resulting in insufficient adsorption performance.

Method used

Nanoconcave and concave rock stone and natural plant active ingredients are used to stabilize synergistically, and the concave rock stone / sodium alginate porous crosslinking membrane is constructed through green water-based Pickering foam template method and calcium ion crosslinking technology to optimize process conditions to improve the porous structure and adsorption of the membrane. performance.

Benefits of technology

It realizes efficient separation/enrichment of uranium, and the membrane material has excellent stability, acid and alkali resistance and mechanical strength, which reduces the preparation cost, is suitable for uranium-containing wastewater treatment, and the material can naturally degrade and does not cause environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a green construction method of an attapulgite / sodium alginate porous cross-linked membrane and a uranium separation / enrichment method of the attapulgite / sodium alginate porous cross-linked membrane. The method comprises the following steps: firstly, adding attapulgite modified by active substances in saponin-rich plants into a sodium alginate / glycerol mixed solution to prepare a membrane forming solution containing Pickering foam; and carrying out film casting and calcium ion crosslinking to obtain the attapulgite / sodium alginate porous cross-linked membrane, and applying the attapulgite / sodium alginate porous cross-linked membrane to efficient separation / enrichment of uranium in a water body. According to the preparation method disclosed by the invention, natural nanostructure clay minerals and plant active components are utilized to synergistically stabilize water-based foam, and further through green processes such as film casting, ionic crosslinking and the like and condition optimization, a thin film material with a porous crosslinking structure, acid and alkali resistance, excellent stability and adsorption performance is constructed; the uranium in the water body can be separated and enriched at low cost and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for constructing a thin film material and using it to separate / enrich uranium, and in particular to a method for green construction of a attapulgite / sodium alginate porous cross-linked membrane and its application in separation / enrichment of uranium in water. Background Art

[0003] People have developed a variety of methods for efficient separation / enrichment of uranium in water, including ion exchange, chemical precipitation, membrane separation, biological methods, adsorption, photocatalysis, etc. These methods have shown application potential. Among them, the adsorption method is widely used due to its high purification coefficient, low cost and simple process. The focus and key lies in the development of low-cost, high adsorption capacity, fast adsorption rate and stable performance adsorbents. However, the single adsorbent has low selectivity for uranium and unsatisfactory adsorption effect, while the composite adsorbent has the defects of high preparation cost, difficult recovery, instability and potential environmental pollution. Therefore, it is crucial to construct a high adsorption performance and environmentally friendly adsorbent in a green and economical way for the separation / enrichment of uranium in water.

[0004] Sodium alginate is a polysaccharide biopolymer extracted from kelp. It has the characteristics of wide sources, easy degradation, good biocompatibility and excellent film-forming properties. It is widely used in food, packaging, medicine and cosmetics industries. In addition, its molecular chain contains a large number of -COOH and -OH functional groups, which can be used as adsorbed functional groups. However, sodium alginate has defects such as strong hydrophilicity and poor mechanical properties when used as a membrane material or adsorption material, which limits its practical application. Various inorganic nanoparticles (such as clay minerals, silica) and polymer materials (such as chitosan and carboxymethyl cellulose) are usually introduced to prepare composite materials or functional modifications to improve application performance and expand application areas. Chinese invention patent CN115837268A discloses a method for strengthening sodium alginate hydrogel by modified attapulgite: sodium alginate and titanium / cerium modified attapulgite are stirred with water and ultrasonically treated to obtain a uniform suspension, which is then dropped into a calcium ion solution to obtain beads, and then freeze-dried to obtain modified attapulgite strengthened sodium alginate hydrogel, which can selectively adsorb inositol hexaphosphate in water; CN105013450B discloses a sodium alginate / carboxymethyl cellulose bifunctional microsphere adsorption material loaded with bimetallic acid and a preparation method thereof: sodium alginate and carboxymethyl cellulose composite sol is first electrosprayed on a receiving device for a metal ion solution to obtain gel microspheres loaded with metal ions, and then calcium cross-linked to obtain a functional microsphere adsorption material, which can adsorb anions such as fluoride ions and cations such as uranyl radicals; CN116532093A discloses a composite adsorption material and its preparation method and application: montmorillonite, agar and sodium alginate to prepare hydrospheres, and then the hydrospheres and Bacillus cereus are cultured together to obtain a gel composite adsorption material for the treatment of low-concentration uranium-containing wastewater; CN108940225B discloses a method for preparing sodium alginate / amino mesoporous silica gel spheres for treating low-concentration uranium-containing wastewater and its application: firstly, disordered mesoporous silica is prepared and grafted with amino groups, and it is blended with sodium alginate solution to obtain a sol, and the sol particles are cross-linked with calcium ions to obtain sodium alginate / amino mesoporous silica gel spheres, which can be used for treating low-concentration uranium-containing wastewater; CN104941592A discloses a magnetic biomaterial for adsorbing uranium (VI) in aqueous solution and its preparation method: recombinant brewer's yeast containing human liver metallothionein gene is mixed with ferromagnetic fluid, and solidified with sodium alginate and calcium chloride to obtain magnetic bioadsorption microspheres for adsorbing uranium (VI) in aqueous solution.

[0005] Although a lot of research has been done on the separation / enrichment of uranium using sodium alginate microspheres, the preparation process of sodium alginate microspheres is relatively complicated. The high concentration of calcium ions used for cross-linking requires multiple washings, and post-processing steps such as freeze drying are required. The particle size of the prepared microspheres is mostly 3 to 6 mm. At the same time, if a film with a length, width, and thickness of 2.0, 2.0, and 0.1 cm (volume and surface area are 0.4 cm, respectively) is used, the size of the prepared microspheres is 2.0, 2.0, and 0.1 cm. 3 and 8.8cm 2) The number of microspheres with the same volume of microspheres prepared was 95, 28, and 12 respectively with a radius of 0.10, 0.15, or 0.20 cm, and the total surface areas of the corresponding microspheres were 11.93, 7.91, and 6.03 cm 2 That is, the same volume of film-forming liquid is used to prepare microspheres and films respectively. Only when the radius of the microspheres is small enough (<0.113 cm), the total surface area of ​​the microspheres can be greater than the surface area of ​​the film, and the preparation process difficulty and cost of small-size microspheres are higher than those of the cast film method. Therefore, compared with microsphere adsorbents, film adsorbents have the advantages of large specific surface area, simple preparation process and high efficiency. In addition, when the microsphere adsorbent is dropped into a calcium ion aqueous solution, the cross-linking rate and degree of the outer surface of the microspheres are much higher than those inside. A large number of adsorption functional groups such as hydroxyl and carboxyl groups inside are not effectively utilized. Even the outer layer with high cross-linking density will limit or prevent large-radius ions from entering the interior of the microspheres, resulting in the need to improve the separation efficiency and rate of uranium by sodium alginate microspheres.

[0006] Using natural plant active ingredients or clay minerals as stable particles and constructing porous adsorbents through the aqueous foam template method is a new method that is greener, more efficient and cleaner. Among them, the peel or seed shell of natural plants rich in saponins contains leached bioactive molecules, including saponins, flavonoids and polysaccharide compounds, which can effectively reduce interfacial tension as surfactants and form rich foam structures in an instant after stirring. However, water-based foams stabilized by plant active ingredients can only last for a few minutes and have poor stability. In addition, attapulgite, which has a unique nanorod crystal structure, large specific surface area, surface activity and good chemical stability, has attracted widespread attention as a solid stable particle. However, it has been reported that when attapulgite is used as a solid particle to stabilize water-based foams, porous composite materials with rich and uniform pores can only be obtained at high solid content (15-20wt.%). Large-scale addition is not desirable for the resource utilization and high-value utilization of attapulgite minerals. On this basis, the present invention systematically analyzes the efficient separation / enrichment method of uranium in water and the application of sodium alginate-based adsorption materials in uranium separation technology in water. Nano-attapulgite and natural plant active ingredients are used as synergistic stabilizers, and a mixed aqueous solution of sodium alginate and glycerol is used as a continuous phase. Through a combination of green water-based Pickering foam template method and calcium ion crosslinking, a attapulgite / sodium alginate porous crosslinked membrane material is constructed, and the separation / enrichment behavior of the porous crosslinked membrane material in uranium in water is further comprehensively analyzed and evaluated, providing a method for separating / enriching uranium using a porous crosslinked membrane. This technology or process can be used as a green functional composite membrane material to solve the problem of efficient separation / enrichment of uranium in water and one of the potential ways to safely treat uranium-containing wastewater. Moreover, there are no related research reports on this technology, and there is no precedent for its application. Summary of the invention

[0007] In view of the ecological and environmental hazards caused by the above-mentioned uranium-containing wastewater, the difficulties in efficient separation / enrichment of uranium in water bodies, and the shortcomings of sodium alginate-based materials in uranium separation applications, the present invention provides a green construction method of a attapulgite / sodium alginate porous cross-linked membrane on the basis of fully recognizing the efficient separation / enrichment method of uranium in water bodies and the water-based foam template method for constructing porous adsorption materials. The attapulgite / sodium alginate porous cross-linked membrane has excellent uranium separation / enrichment performance, stability and acid and alkali resistance, and can be applied to the fields of efficient separation / enrichment of uranium in water bodies and treatment of uranium-containing wastewater.

[0008] The green construction method of the attapulgite / sodium alginate porous cross-linked membrane of the present invention comprises the following steps: (1) The peel or seed shell of a saponin-rich plant is washed with water, dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain plant powder; the plant powder and dissociated attapulgite powder are uniformly dispersed in deionized water, and ultrasonically treated for 5 to 15 minutes to obtain a uniform modified attapulgite suspension, wherein the mass ratio of plant powder: attapulgite: water is 1 to 2: 5 to 10: 100; The saponin-rich plant is at least one of angelica, soapberry, saponin, codonopsis, liquorice and quinoa. The dissociated attapulgite powder has a attapulgite content of ≥70% and a rod crystal length of ≥0.9 μm. The ultrasonic treatment is performed by using a cell disruptor at room temperature and a power of 200 to 500 W.

[0009] The dissociated attapulgite is a nanometer powder obtained by crushing and rolling the natural attapulgite ore, adding water to make pulp and hydration for 6 hours, and then sequentially undergoing cyclone classification treatment, ultrasonic dissociation treatment and strong drying, wherein the ultrasonic dissociation treatment is an ultrasonic treatment for 5 to 10 minutes at an ultrasonic frequency of 20 to 40kHz and a power density of 40 to 60W / L; the crushing is to crush the attapulgite to 50 to 100 meshes; the temperature of the strong drying treatment is 90 to 110°C, and the classification frequency is 5 to 15Hz. Alternatively, the dissociated attapulgite is a nanometer powder obtained by crushing and rolling the natural attapulgite ore, making pulp and hydration for 6 hours, and then sequentially undergoing cyclone classification treatment, high-pressure homogenization treatment and strong drying, wherein the high-pressure homogenization treatment is carried out at a pressure of 30 to 50MPa; the crushing is to crush the attapulgite to 50 to 100 meshes; the temperature of the strong drying treatment is 90 to 110°C, and the classification frequency is 5 to 15Hz.

[0010] (2) Add the modified attapulgite suspension to a sodium alginate / glycerol mixed aqueous solution (the mass fractions of sodium alginate and glycerol are 2% and 0.4%, respectively) at a volume ratio of 1:1 to 1:2, and stir at 6000 to 10000 rpm for 5 to 10 min to form a uniform film-forming liquid; cast the film-forming liquid into a film (the film thickness is 0.5 to 1.0 mm), and add a water-soluble calcium salt solution with a mass fraction of 0.5 to 1.0% to completely immerse the film. After 2 to 4 hours, take out the film and wash it with deionized water for 3 to 5 times to obtain a attapulgite / sodium alginate porous cross-linked film. The water-soluble calcium salt is at least one of calcium chloride, calcium iodide, calcium dihydrogen phosphate or calcium nitrate. Preferably, the porous cross-linked wet film is vacuum dried at 40 to 50°C and a vacuum degree of 0.05 to 0.08 MPa for 8 to 12 hours to obtain a attapulgite / sodium alginate porous cross-linked film.

[0011] Particle size has a significant impact on the formation and performance of Pickering foam, and nanoparticles have a large diffusion coefficient and dispersibility. At low addition levels, they can be quickly adsorbed and densely arranged on the foam surface to form a dense mechanical barrier film, which effectively prevents the collision and aggregation of bubbles and increases the mutual repulsion between bubbles, effectively improving the stability of the foam structure. Figure 1 As shown in Table 1, under the strong cavitation, shear, collision and temperature effects brought by low-frequency high-power ultrasonic dissociation or high-pressure homogenization dissociation, the dispersibility of the rod crystals of the dissociated attapulgite is significantly improved, and a large number of rod crystal aggregates have been non-destructively and efficiently dissociated, with a particle size distribution of D 50 The dissociated attapulgite also has a larger specific surface area (from 186.04m 2 / g increases to 214.85 or 234.05m 2 / g), a large number of highly dispersed rod crystals are irregularly arranged to form a large number of stacked pores (the total pore volume is also increased from 0.31cm 3 / g increases to 0.34 or 0.39cm 3 / g), which is beneficial to the subsequent modification and loading of plant active substances; in addition, the initial and 10-min shear rotational viscosities of the dissociated attapulgite are much higher than those before dissociation. Better suspension stability and colloidal properties are beneficial to improving the long-term stability of Pickering foam, and the attapulgite with a large length / diameter ratio has better viscosity-increasing and stabilizing effects on the water-based foam system after dissociation of rod crystal bundles.

[0012] Furthermore, the present invention selects active ingredients from saponin-rich plants to modify dissociated attapulgite, and preferably uses the modified attapulgite as a stabilizer for aqueous foam, that is, using plant active ingredients and nano-clay minerals to synergistically stabilize aqueous foam, wherein the cell disruption process helps to quickly and fully dissolve the active components from saponin plants, and effectively improves the modification efficiency and the dispersibility of modified nanoparticles in the suspension; and further optimizes the addition amount of key components such as plant powder, attapulgite, and sodium alginate / glycerol mixed aqueous solution, to obtain a film-forming solution with a stable and uniform foam structure. From the optical microscope photo of the film-forming solution ( Figure 2 ) It can be seen that the film-forming liquid prepared after optimizing the composition is composed of a large number of circular bubbles of similar size and uniform dispersion and viscoelastic liquid. The bubbles have not coarsened or agglomerated, and the viscosity and fluidity of the film-forming liquid meet the conditions for film casting. The uniform and stable presence of bubbles in the film-forming liquid ensures the retention and uniform distribution of the porous structure during the subsequent ionic cross-linking process. This is attributed to the fact that the attapulgite fully modified with saponin will be adsorbed on the air-water interface, providing a protective barrier for the bubbles, increasing the bubble stability and liquid film strength. At the same time, the attapulgite particles in the continuous phase will also form a three-dimensional network structure, which increases the viscosity of the foam and inhibits the flow of bubbles and liquid, thereby greatly improving the stability of the foam and the overall strength of the porous membrane material.

[0013] Unlike the conventional membrane material preparation step of standing and degassing, the present invention directly casts the uniform and rich foam film-forming liquid to prepare a liquid film with a thickness of 0.5 to 1.0 mm, and adds a water-soluble calcium salt solution with a mass fraction of 0.5 to 1.0% to the surface of the liquid film to completely immerse the liquid film, and after 2 to 4 hours, the above film is taken out and washed 3 to 5 times with deionized water to obtain a attapulgite / sodium alginate porous cross-linked film. In the preparation process of the membrane material, the thickness of the liquid film is controlled by adding the mass of the membrane-forming liquid, which is conducive to the full cross-linking of the film with the calcium ions in the solution, and retains the original uniform foam and porous composite structure. At the same time, the washed attapulgite / sodium alginate porous membrane is directly cross-linked with calcium without drying. Too low calcium ion concentration leads to insufficient cross-linking, which greatly reduces the mechanical strength and toughness of the cross-linked membrane. Too high calcium ion concentration will mask or cover a large number of active adsorption functional groups, reducing the adsorption and separation efficiency of the final porous cross-linked membrane. After experimental optimization, the porous cross-linked membrane has excellent adsorption and separation efficiency after cross-linking with 0.5-1.0% water-soluble calcium salt solution under the same conditions. When added to uranium-containing wastewater with a uranium concentration of 200ppm and a pH value of 6, the uranium adsorption amount and removal rate reach 336mg / g and 88.30%, respectively. By controlling the volume ratio of the sodium alginate / glycerol mixed aqueous solution to the modified attapulgite suspension, the stirring speed, and time, etc., a pore-adjustable attapulgite / sodium alginate porous cross-linked membrane ( Figure 3 ). From the TEM image of the membrane ( Figure 4) It can be seen that the microscopic morphology of the membrane prepared by the present invention is a porous cross-linked structure, and the highly dispersed nano-attapulgite rod crystals are evenly distributed inside the membrane material, which is conducive to increasing the mechanical strength of the membrane and forming a dense and complex porous structure. Preferably, the washed porous cross-linked membrane can be vacuum dried, which is conducive to forming a highly connected pore structure inside the membrane material and increasing the total adsorption sites of the material.

[0014] The changes of the attapulgite / sodium alginate porous cross-linked membrane immersed in solutions with different pH values ​​(1, 5, 9, 13) ( Figure 5 ) It can be seen that in a neutral water environment, the pure sodium alginate film was completely dissolved within 3 minutes, while the attapulgite / sodium alginate porous cross-linked film still maintained its original shape after being immersed in a strong acid or strong base solution for 14 days; similarly, in the batch adsorption experiment, it was also found that the porous cross-linked film still maintained its original film shape after 24 hours of shock reaction with the uranium-containing solution, indicating that it has good acid and alkali resistance. From the thermogravimetric curve and the differential thermogravimetric curve ( Figure 6 ) It can be seen that the residual mass of pure sodium alginate membrane, calcium cross-linked membrane and attapulgite / sodium alginate porous cross-linked membrane heated to 800°C is 26.33%, 50.35% and 57.83% respectively; compared with pure sodium alginate membrane, the maximum weight loss peak of calcium cross-linked membrane and attapulgite / sodium alginate porous cross-linked membrane shifts to the high temperature region, and the mass loss rate in the range of 200-300°C is -3.48% / °C and -2.34% / °C respectively, which is much lower than that of pure sodium alginate membrane (-10.04% / °C), which indicates that attapulgite / sodium alginate porous cross-linked membrane has excellent structural stability. The improvement of acid and alkali resistance and structural stability has laid a foundation for the application of attapulgite / sodium alginate porous cross-linked membrane in the separation / enrichment of uranium in water and the treatment of uranium-containing wastewater.

[0015] The method for uranium separation / enrichment using the attapulgite / sodium alginate porous cross-linked membrane constructed by the patented method is characterized in that the specific steps are: adjusting the pH value of the uranium-containing water body with a U(VI) concentration of 2 to 300 ppm to 5.0 to 7.0, adding 0.2 to 2.0 g / L of the attapulgite / sodium alginate porous cross-linked membrane thereto, shaking or stirring the reaction at room temperature for 60 to 240 minutes, determining the uranium concentration in the solution, and calculating the uranium separation efficiency If the uranium separation efficiency is ≥97%, the porous cross-linked membrane is removed from the water body to achieve the separation / enrichment of uranium in the water body; if the calculated uranium separation efficiency is <97%, the porous cross-linked membrane can be removed from the water body, and a new porous cross-linked membrane can be added to the uranium-containing water body again, and the treatment is circulated until the uranium separation efficiency is ≥97%.

[0016] Figure 7The following are microscope photos of the attapulgite / sodium alginate porous cross-linked membrane prepared by the present invention before and after adsorption and separation of uranium. In the initial state, the porous cross-linked membrane contains a large number of vesicle-like structures and appears milky white. After adsorbing uranium, the porous cross-linked membrane appears uniformly yellow (uranyl). The colorimeter was used to test the color of the porous cross-linked membrane. L*, a* and b* 21.75±0.07, -0.44±0.01 and -1.34±0.02 respectively. L*, a* and b* The chromaticity values ​​were 37.55±1.70, -4.14±0.79 and 22.51±0.82 respectively. b* The value changed from negative to +22.5, confirming that the porous cross-linked membrane turned yellow after uranium adsorption. Further, under the microscope, it was observed that uranyl was evenly distributed on the surface or inside the vesicle structure, and the vesicle structure and surface pores increased the contact area between the porous cross-linked membrane and uranium, promoting the rapid adsorption and efficient enrichment of uranium. From the FTIR spectra before and after uranium adsorption ( Figure 8 ) by comparison, it can be found that an obvious O=U=O characteristic peak (908.7cm −1 ), indicating that the uranyl ions are chemically bonded to the porous cross-linked membrane, and the stretching vibration peak of C=O is weakened and red-shifted (from 1632 to 1628 cm -1 ) confirmed the coordination reaction between carboxyl and uranyl ions. We further conducted XPS spectrum analysis before and after uranium adsorption. The full spectrum after adsorption ( Fig. 9 a) shows obvious U characteristic peaks (U4f5, U4f7, U4d3, U4d5), indicating that uranium is adsorbed and fixed on the porous cross-linked membrane; high-resolution U4f spectrum ( Fig. 9 b) The binding energies are 392.6eV and 381.7eV, respectively, indicating that the valence state of uranium is +6, indicating that the adsorption process is mainly based on coordination reaction and does not involve reduction reaction; high-resolution C1s and Ca2P spectra ( Fig. 9 The change in binding energy in (c, d) indicates a change in the electron cloud density, indicating that the interaction between the porous cross-linked membrane and uranium includes at least the coordination reaction between the carboxyl group in calcium alginate and uranium and the substitution reaction between uranium and calcium ions, and that multiple reactions synergistically improve the adsorption and separation efficiency of uranium.

[0017] Furthermore, the separation / enrichment performance of the attapulgite / sodium alginate porous cross-linked membrane prepared by the present invention for uranium was systematically investigated. The attapulgite / sodium alginate porous cross-linked membrane with a solid-liquid ratio of 2.0 g / L or the vacuum-dried porous cross-linked membrane with a solid-liquid ratio of 0.2 g / L was added to a water body with a uranium concentration of 3 to 300 ppm. The adsorption thermodynamic curve is as follows: Fig.10As shown in (a) and 10 (b), both show excellent uranium separation efficiency. When added at a solid-liquid ratio of 0.2 g / L, the uranium removal rate in the low concentration area (3-20 ppm) is >97%, and the adsorption amount in the high concentration area (100-300 ppm) can reach up to 500 mg / g. The porous cross-linked membrane that has not been dried also shows a high uranium separation efficiency, and it also effectively avoids the need for secondary swelling of the dry membrane when entering the water body, thereby increasing the adsorption equilibrium time. The adsorption model fitting confirmed that the adsorption isotherm of uranium on the attapulgite / sodium alginate porous cross-linked membrane fits well with the Langmuir adsorption isotherm, and the linear correlation coefficient R 2 They are 0.99992 (10(a)) and 0.99623 ( Fig.10 (b) confirms that uranium is enriched in a monolayer adsorption mode on the porous cross-linked membrane. From the adsorption kinetics curve ( Fig.10 (c) It can be seen that the membrane material prepared based on the present invention has a unique porous cross-linked structure and rich adsorption functional groups. The adsorption of uranium on the attapulgite / sodium alginate porous cross-linked membrane is a rapid adsorption process, and the adsorption equilibrium is reached in about 1 hour. The faster adsorption rate is helpful for the application of porous cross-linked membrane materials in uranium interception, adsorption separation and other aspects in water bodies. The porous cross-linked membrane has excellent acid and alkali resistance and can be quickly desorbed in a highly alkaline environment without affecting the subsequent recycling performance. In addition, how to quickly and efficiently separate the adsorption saturated adsorbent from the liquid phase is also one of the specific application technical difficulties. After the adsorption equilibrium, the uranium separation efficiency was compared and analyzed in two cases: directly removing the porous cross-linked membrane prepared by the present invention from the uranium-containing water body and taking the supernatant after centrifugal treatment. From the example Fig.10 (d) It can be seen that under different solid-liquid ratios, there is almost no difference in the uranium adsorption amount and removal rate after solid-liquid separation and centrifugal separation. This shows that uranium is firmly adsorbed on the porous cross-linked membrane through chemical bonds, and no uranium precipitation is generated during the process. This is conducive to the application of the porous cross-linked membrane material prepared by the present invention in special scenarios such as high-concentration uranium-containing wastewater and nuclear accident wastewater treatment through step-by-step adsorption and multiple addition modes.

[0018] In summary, the present invention has the following advantages compared with the prior art: 1. The present invention adds dissociated nano-attapulgite modified with saponin plant active substances into a sodium alginate / glycerol mixed solution, utilizes natural nanostructured clay minerals and plant active ingredients to synergistically stabilize aqueous foam, and prepares a film-forming liquid rich in Pickering foam and active adsorption functional groups, and then through green combination processes such as cast film and calcium ion crosslinking and condition optimization, a attapulgite / sodium alginate porous crosslinked membrane with comprehensive properties such as porous crosslinked structure, large specific surface area, acid and alkali resistance, excellent adsorption performance, stability and mechanical strength is constructed, which is beneficial to solving the ecological and environmental hazards caused by uranium-containing wastewater and the problems of efficient separation / enrichment of uranium in water bodies.

[0019] 2. The present invention makes efficient use of the nanostructure characteristics and plant active ingredients of attapulgite. Through green and efficient processes such as foam template method and ion cross-linking, a large number of active uranium-absorbing groups (carboxyl, hydroxyl, etc.) and replaceable ions (calcium, magnesium, etc.) are evenly distributed in the pores and vesicle structures of the prepared attapulgite / sodium alginate porous cross-linked membrane. Under various modes such as low addition amount, wet membrane, dry membrane, etc., uranium in 2-300ppm uranium-containing water can be quickly and efficiently separated / enriched. That is, the complementary and synergistic effects of adsorption method and membrane separation method are fully utilized to achieve the separation and enrichment of uranium in water with low cost, high efficiency and universality, and it has good application and promotion prospects.

[0020] 3. The method for constructing the porous cross-linked attapulgite / sodium alginate membrane of the present invention and the method for applying the same to uranium separation / enrichment effectively utilizes a combination of processes such as mineral nano-sizing, high-pressure homogenization, film casting, and ionic cross-linking to promote the construction of functional composite thin film materials and the improvement of uranium separation / enrichment performance. The entire preparation process and application process do not involve the use of high-temperature and high-pressure equipment, the reaction conditions are mild, the process is easy to control and is green and environmentally friendly, and it is easy to achieve industrial mass production. Moreover, after the attapulgite / sodium alginate porous cross-linked membrane separates / enriches uranium, it can be naturally degraded after desorption and disposal, and the degradation products are natural small molecules and minerals, which will not cause secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The change of the dispersibility of the rod crystals before and after the dissociation treatment of the attapulgite in the present invention (left: before the dissociation treatment of the attapulgite, right: after the dissociation treatment of the attapulgite).

[0022] Figure 2 Optical microscope photos of the film-forming solution prepared in the present invention (left: x10 times, right: x40 times).

[0023] Figure 3 The present invention provides attapulgite / sodium alginate porous cross-linked membranes with different pore sizes.

[0024] Figure 4 This is a TEM image of the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention.

[0025] Figure 5 The graph shows the changes of the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention when immersed in solutions with different pH values.

[0026] Figure 6 Thermogravimetric curves (left) and differential thermogravimetric curves (right) of the pure sodium alginate membrane, the pure sodium alginate membrane after calcium cross-linking, and the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention.

[0027] Figure 7 Microscope photos of the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention (left) and after uranium adsorption (right).

[0028] Figure 8 FTIR spectra of the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention before and after uranium adsorption.

[0029] Fig. 9 The XPS spectra of the attapulgite / sodium alginate porous cross-linked membrane prepared by the present invention before and after uranium adsorption, wherein a is the full XPS spectrum; b is the U fine spectrum; c is the C fine spectrum; d is the Ca fine spectrum.

[0030] Fig.10 The separation / enrichment performance of the attapulgite / sodium alginate porous cross-linked membrane prepared in the present invention for U(VI) (a, b-adsorption thermodynamic curves at solid-liquid ratios of 2.0 and 0.2 g / L, c-adsorption kinetic curve, d-influence of solid-liquid separation on separation efficiency). DETAILED DESCRIPTION

[0031] The green construction of the attapulgite / sodium alginate porous cross-linked membrane and the method for separating / enriching uranium of the present invention are further described below through specific examples.

[0032] In the present invention, a sodium alginate / glycerol mixed solution (the mass fractions of sodium alginate and glycerol are 2% and 0.4%, respectively) is stirred at 500 rpm, 100 g of sodium alginate and 20 g of glycerol are dissolved in 5 L of water, and the uniform solution obtained after continuous stirring for at least 24 hours is set aside. The effects of the initial uranium concentration (3-300 ppm), contact time (30-480 min), and whether solid-liquid separation is performed on the separation / enrichment performance of utahedralite / sodium alginate porous cross-linked membrane for uranium are evaluated by static intermittent adsorption experiments. Specifically, the above-mentioned porous cross-linked membrane is added to a uranium-containing aqueous solution, and then placed in a constant temperature shaker to reach adsorption equilibrium at 160 rpm and 25°C. The uranium concentration in the solution before and after adsorption is analyzed by UV-vis spectroscopy at a maximum wavelength of 652 nm. The removal rate of the sample ( R , %) and adsorption amount ( Q t , mg / g).

[0033] In the formula, C 0 and Ct (mg / L) are the initial and final concentrations of uranium in the uranium-containing aqueous solution, V (mL) is the volume of the uranium-containing aqueous solution, m(mg) is the mass of the porous cross-linked membrane.

[0034] Comparative Example 1 The above sodium alginate / glycerol mixed solution was used as the film-forming solution. 10 ml of the film-forming solution was placed in a plastic tray with a diameter of 10 cm for casting and dried at room temperature to obtain a pure sodium alginate film (labeled as pure SA film). Figure 4 As shown, it has a strong hydrophilicity and will dissolve quickly and completely once in contact with water, making it unsuitable for separation / enrichment of uranium in water.

[0035] Comparative Example 2 Take 75mL of sodium alginate / glycerol mixed solution and mix it with 25mL of water to form a film-forming solution. Take 10mL of the film-forming solution each time and place it in a plastic tray with a diameter of 10cm to form a film. Add 3.0% calcium chloride solution by mass to completely immerse the liquid film. After 2 hours, take out the above film and wash it with deionized water for 3 times to obtain a sodium alginate cross-linked film. Figure 5 As shown in Figure 2, after calcium crosslinking, the thermal stability of the film material is greatly improved. Further, the above sodium alginate crosslinked film is added to a solution with a solid-liquid ratio of 0.5 g / L at a concentration of 8*10 -4 M (190ppm) uranium-containing water, the pH value of the system was adjusted to 6.0, and after 240min of oscillation reaction, the uranium adsorption amount and removal rate were measured and calculated to be 194.78mg / g and 51.15% respectively.

[0036] Example 1 The method for constructing a attapulgite / sodium alginate porous cross-linked membrane and separating / enriching uranium therefrom comprises the following steps: (1) Wash the sapodilla fruit with water, dry it to constant weight, crush it, and pass it through a 200-mesh sieve to obtain plant powder; evenly disperse the above plant powder and ultrasonically dissociated attapulgite powder in deionized water, and treat it with ultrasonic cell disruption for 15 minutes (power is 200w) to obtain a modified uniform attapulgite suspension (the mass ratio of plant powder: attapulgite: water is 1:5:100). Among them, the dissociated attapulgite is a nanopowder obtained by crushing the natural attapulgite ore (<100 mesh) and rolling it, adding water to make pulp and hydration for 6 hours, and then successively undergoing cyclone classification treatment, ultrasonic dissociation treatment (ultrasonic treatment at a frequency of 40kHz and a power density of 40W / L for 5 minutes) and strong drying (110℃, 5Hz); after testing, the attapulgite content in the dissociated nanopowder is 75%, and the average length of the rod crystal is about 1.0μm; (2) Add 50 mL of the modified attapulgite suspension to 50 mL of a sodium alginate / glycerol mixed aqueous solution (the mass fractions of sodium alginate and glycerol are 2% and 0.3%, respectively), and stir at 6000 rpm for 10 min to form a uniform film-forming solution. The optical microscope photo of the film-forming solution is shown in Figure 2 8 ml of the solution was placed in a plastic tray with a diameter of 10 cm to form a film (the film thickness was 1.0 mm), and a 0.5% calcium iodide solution was added to completely immerse the film. After 2 h, the film was taken out and washed three times with deionized water to obtain a attapulgite / sodium alginate porous cross-linked film (see Figure 3 Right). As shown in the optical microscope image ( Figure 6 ), after the porous cross-linked membrane reacts with uranium-containing water, the membrane surface appears uniformly yellow, and the FTIR spectrum ( Figure 7 ) further confirmed that uranium was adsorbed on the porous cross-linked membrane.

[0037] Example 2 The method for constructing a attapulgite / sodium alginate porous cross-linked membrane and separating / enriching uranium therefrom comprises the following steps: (1) Wash the fruit of soapberry with water, dry it to constant weight, crush it, and pass it through a 200-mesh sieve to obtain plant powder; evenly disperse the above plant powder and ultrasonically dissociated attapulgite powder in deionized water, and treat it with cell disruption for 5 minutes (power is 500w) to obtain a modified uniform attapulgite suspension (the mass ratio of plant powder: attapulgite: water is 2:5:100). Among them, the dissociated attapulgite is a nanopowder obtained by crushing the natural attapulgite ore (<100 mesh) and slurrying and hydrating it for 6 hours after rolling, and then undergoing cyclone classification treatment, high-pressure homogenization treatment and strong drying (110℃, 5Hz), wherein the high-pressure homogenization treatment is carried out under a pressure of 30MPa; after testing, the attapulgite content in the dissociated nanopowder is 80%, and the average length of the rod crystal is about 0.9μm; (2) Add 25 mL of the modified attapulgite suspension to 50 mL of a sodium alginate / glycerol mixed aqueous solution (the mass fractions of sodium alginate and glycerol are 2% and 0.4%, respectively), and stir at 10,000 rpm for 5 min to form a uniform film-forming solution; take 4 mL of the film-forming solution and place it in a plastic tray with a diameter of 10 cm to cast a film (the film thickness is 0.5 mm), and add a 1.0% calcium nitrate solution to completely immerse the film. After 4 h, take out the above film and wash it with deionized water 5 times to obtain a attapulgite / sodium alginate porous cross-linked membrane (see Figure 3 Left). Further, the above-mentioned attapulgite / sodium alginate porous cross-linked membrane was added to a water body with a uranium concentration of 3 to 300 ppm and a pH value of 6 ± 0.1 at a solid-liquid ratio of 2.0 g / L. The adsorption thermodynamic curve is as follows: Fig. 9 (a) shown.

[0038] Example 3 The method for constructing a attapulgite / sodium alginate porous cross-linked membrane and separating / enriching uranium therefrom comprises the following steps: (1) Wash quinoa shells with water, dry to constant weight, crush and pass through a 200-mesh sieve to obtain plant powder; the plant powder and ultrasonically dissociated attapulgite powder are uniformly dispersed in deionized water, and subjected to cell disruption treatment for 15 minutes (power of 500W) to obtain a modified uniform attapulgite suspension (the mass ratio of plant powder: attapulgite: water is 1:10:100), wherein the dissociated attapulgite is a nanopowder obtained by crushing natural attapulgite ore (<100 mesh) and rolling it for 6 hours, and then subjecting it to cyclone classification treatment, ultrasonic dissociation treatment (ultrasonic treatment at a frequency of 20kHz and a power density of 60W / L for 10 minutes) and strong drying (110℃, 5Hz); the test shows that the attapulgite content in the dissociated nanopowder is 80%, and the average length of the rod crystal is about 0.9μm; (2) Add 25 mL of the modified attapulgite suspension to 50 mL of a sodium alginate / glycerol mixed aqueous solution (the mass fractions of sodium alginate and glycerol are 2% and 0.4%, respectively), and stir at 10,000 rpm for 10 min to form a uniform film-forming liquid; take 8 ml of the film-forming liquid and place it in a plastic tray with a diameter of 10 cm to cast a film (the thickness of the liquid film is 1.0 mm), and add a 1.0% mass fraction of calcium dihydrogen phosphate solution to completely immerse the liquid film. After 2 h, take out the above-mentioned film and wash it three times with deionized water; finally, the washed porous cross-linked film is vacuum dried at 40 ° C and a vacuum degree of 0.08 MPa for 12 h to obtain a attapulgite / sodium alginate porous cross-linked membrane. Further, the above-mentioned attapulgite / sodium alginate porous cross-linked membrane was added to the uranium concentration of 8*10 at pH values ​​of 5.0, 6.0, and 7.0 at a solid-liquid ratio of 1.0 g / L, 0.5 g / L, and 0.2 g / L, respectively. -4 M (190ppm) in water, after adsorption equilibrium, the membrane was directly removed and the supernatant was taken or the supernatant was taken after centrifugation at 4000rpm for 5min. The corresponding uranium separation efficiency is as follows Fig. 9 (d) shown.

[0039] Example 4 The method for constructing a attapulgite / sodium alginate porous cross-linked membrane and separating / enriching uranium therefrom comprises the following steps: (1) Wash the fruit of soapberry with water, dry it to constant weight, crush it, and pass it through a 200-mesh sieve to obtain plant powder; evenly disperse the plant powder and ultrasonically dissociated attapulgite powder in deionized water, and subject it to cell disruption treatment for 10 minutes (power is 500w) to obtain a modified uniform attapulgite suspension (the mass ratio of plant powder: attapulgite: water is 2:10:100), wherein the dissociated attapulgite is a nano-powder obtained by crushing natural attapulgite ore (<100 mesh) and slurrying and hydrating it for 6 hours after rolling, and then subjecting it to cyclone classification treatment, high-pressure homogenization treatment and strong drying (110℃, 5Hz), wherein the high-pressure homogenization treatment is carried out under a pressure of 50MPa; after testing, the attapulgite content in the dissociated nano-powder is 80%, and the average length of the rod crystal is about 0.9μm; (2) Add 50 mL of the modified attapulgite suspension to 50 mL of a sodium alginate / glycerol mixed aqueous solution (the mass fractions of sodium alginate and glycerol are 2% and 0.4%, respectively), and stir at 6000 rpm for 10 min to form a uniform film-forming liquid; take 8 ml and place it in a plastic tray with a diameter of 10 cm to cast a film (the thickness of the liquid film is 1.0 mm), and add a 1.0% mass fraction of calcium chloride solution to completely immerse the liquid film. After 4 hours, take out the above film and wash it with deionized water 5 times; finally, the washed porous cross-linked film is vacuum dried at 50°C and a vacuum degree of 0.05 MPa for 8 hours to obtain a attapulgite / sodium alginate porous cross-linked film. Furthermore, the above attapulgite / sodium alginate porous cross-linked film is added to a water body with a uranium concentration of 3-300 ppm and a pH value of 6±0.05 at a solid-liquid ratio of 0.2 g / L. Its adsorption thermodynamic curve and kinetic curve are as follows Fig. 9 (b) and 9 (c); FTIR and XPS comparative analysis of membrane materials before and after adsorption is shown in Figure 7 and 8 shown.

[0040] Example 5 The method for stepwise separation / enrichment of uranium in water using a attapulgite / sodium alginate porous cross-linked membrane comprises the following steps: The attapulgite / sodium alginate porous cross-linked membrane prepared in Example 4 was added to a liquid-solid ratio of 0.5 g / L to a solution having a pH value of 6.0 and a uranium concentration of 8*10 -4 M (190ppm) in water, after 120min of oscillation reaction, the uranium separation efficiency was determined to be 72.34%. After the porous cross-linked membrane was removed, a new porous cross-linked membrane was added to the uranium-containing water again. After 60min of oscillation reaction, the total uranium separation efficiency was determined to be 97.76%. The two-stage treatment achieved efficient separation / enrichment of uranium in uranium-containing water.

Claims

1. A green construction method of attapulgite / sodium alginate porous cross-linked membrane, characterized in that: The following steps are involved: (1) The peel or seed shell of a saponin-rich plant is washed with water, dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain plant powder; the plant powder and dissociated attapulgite are uniformly dispersed in deionized water, and ultrasonically treated for 5 to 15 minutes to obtain a uniform modified attapulgite suspension, wherein the mass ratio of plant powder: dissociated attapulgite: water is 1 to 2: 5 to 10: 100; (2) The modified attapulgite suspension is added into a sodium alginate / glycerol mixed aqueous solution in a volume ratio of 1:1 to 2:1, and stirred at 6000 to 10000 rpm for 5 to 10 min to obtain a uniform film-forming solution; the film-forming solution is cast into a film with a film thickness of 0.5 to 1.0 mm, and a water-soluble calcium salt solution with a mass fraction of 0.5 to 1.0% is added to completely immerse the film. After 2 to 4 hours, the film is taken out and washed with deionized water for 3 to 5 times to obtain a attapulgite / sodium alginate porous cross-linked membrane: in the sodium alginate / glycerol mixed aqueous solution, the mass fractions of sodium alginate and glycerol are 2.0% and 0.4%, respectively.

2. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (1), the saponin-rich plant is at least one of angelica sinensis, soapberry, saponin, codonopsis pilosula, liquorice, and quinoa; the attapulgite content in the dissociated attapulgite powder is ≥70%, and the rod crystal length is ≥0.9 μm.

3. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (1), the dissociated attapulgite is a nano powder obtained by crushing natural attapulgite ore, rolling it with a roller and adding water to make pulp for 6 hours, and then subjecting it to cyclone classification treatment, ultrasonic dissociation treatment and strong drying, wherein the ultrasonic dissociation treatment is an ultrasonic treatment at a frequency of 20 to 40 kHz and a power density of 100 to 200 W / L for 5 to 10 minutes.

4. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (1), the dissociated attapulgite is a nano powder obtained by crushing the natural attapulgite ore, rolling it and hydrating it with water for 6 hours, and then subjecting it to cyclone classification, high-pressure homogenization and strong drying, wherein the high-pressure homogenization is carried out at a pressure of 30 to 50 MPa.

5. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (1), the ultrasonic treatment is performed using an ultrasonic cell disruptor at room temperature and a power of 200 to 500 W.

6. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (2), the water-soluble calcium salt is at least one of calcium chloride, calcium iodide, calcium dihydrogen phosphate, and calcium nitrate.

7. The green construction method of a attapulgite / sodium alginate porous cross-linked membrane according to claim 1, characterized in that: In step (2), the washed porous cross-linked membrane is vacuum dried at 40 to 50° C. and a vacuum degree of −0.08 to −0.05 MPa for 8 to 12 hours to obtain a attapulgite / sodium alginate porous cross-linked membrane.

8. Use of the attapulgite / sodium alginate porous cross-linked membrane constructed according to any one of claims 1 to 7 in separation / enrichment of uranium.

9. Use of the attapulgite / sodium alginate porous cross-linked membrane in separation / enrichment of uranium according to claim 8, characterized in that: The method for separating / enriching uranium with a porous cross-linked membrane comprises the following specific steps: adjusting the pH value of a uranium-containing water body with a U(VI) concentration of 2 to 300 ppm to 5.0 to 7.0, adding 0.2 to 2.0 g / L of a porous cross-linked membrane thereto, shaking or stirring the reaction at room temperature for 60 to 240 minutes, determining the uranium concentration in the solution, and calculating the uranium separation efficiency, where the separation efficiency = If the uranium separation efficiency is ≥97%, the porous cross-linked membrane is removed from the uranium-containing water body to achieve uranium separation / enrichment; if the uranium separation efficiency is <97%, the porous cross-linked membrane can be removed and a new porous cross-linked membrane can be added to the uranium-containing water body again, and the treatment is circulated until the uranium separation efficiency is ≥97%.